THE POTENCY OF CUCUMBER (CUCUMIS SATIVUS L.) PEEL EXTRACT AS ANTICHOLESTEROL - Resita Putri; Devina Ingrid Anggraini (Universitas Muhammadiyah Magelang, 2022)
The liver has a very important role in the human body. However, these organ tissues are also very susceptible to be tissue damage. Fatty liver disease (steatosis) is a disease caused by high cholesterol. Physically, cholesterol is a yellowish subtance, lumps like wax, and is an arrangement of steroid groups. Non-alcoholic steatohepatitis (NASH) occurs due to excess cholesterol levels in the liver. Liver function can be affected as a result of liver damage. So, a hepatoprotector is needed. The flavonoid content of cucumber skin has potential as an anticholesterol. The purpose of this research is to analyze the ability of the ethanol extract of cucumber peel (Cucumis sativus L.) as a cholesterol lowering agents as indicated by the EC50 value. Maceration extraction method used in this study using 96% ethanol as solvent. Qualitative analysis of ethanolic extract of cucumber peel is known to have flavonoids, steroids, alkaloids as indicated by the appearance of color changes, and saponins which are indicated by the appearance of foam. Lieberman-burchad reagent was used for quantitative analysis of anticholesterol using a UV-Visible spectrophotometer. The analysis was carried out at a maximum wavelength of 665,0 nm with an incubation time of 15 minutes. The concentration variations of the extract used were between 25-150 with a range of 25 ppm. The results showed that the ethanolic extract of cucumber peel could potentially be an anticholesterol with the percentage reduction of 28.50%; 35.45%; 39.59%; 45.82%; 51.24%; and 55.12% at 5 variations of concentration. The EC50 value was achieved at a concentration of 122.04 ppm.